The satisfaction and usage in the implementation of smart home system / Azian Masiron - Masiron, Azian (2005)
In the world of electronic commerce of today and tomorrow. Smart Home System has been the aim for the developer in housing sector as one of the attraction to homebuyer. Good marketing strategy on Smart Home System can have a broad market appeal to new homebuyers. However, understanding of the capabilities of these systems is currently very limited within the housing industry that lead to the few barriers in the implementation of this system. Despite all their work and aimed at the implementation of Smart Home System, this system remained largely unnoticed by the user and certainly underused because lack of education and guidance to the user. Some of the major impediments to market expansion include perceived of use, perceived usefiilness, perceived credibility, cost, user interfaces (central) controllers/computer software, and mistrust of technology. The issues highlighted here are about the usage, satisfaction and privacy issues in advance technology of Smart Home System. In order to discover the issue, a condominium that will be defined as Condo-X for the confidentially purpose has been selected. Approximately 180 questionnaires were distributed to the residents as a sample to get their opinion regarding the issues. Hopefully, it will improve a better understanding in identifying their usage and satisfaction in practicing this technology. Besides that, there are several recommendations to improve the quality in the implementation of the system for future benefit.